2020
DOI: 10.3390/rel11100496
|View full text |Cite
|
Sign up to set email alerts
|

Religious/Spiritual Referrals in Hospice and Palliative Care

Abstract: This study examines the religious/spiritual referral patterns in hospice and palliative care. Religion and death are two highly intersected topics and albeit often discussed together in hospice and palliative care, little is known about how professionals respond to religious/spiritual needs of patients/families/friends and in relation to the chaplaincy team. By means of an in-depth interviewing method, this paper reports on data from 15 hospice and palliative care professionals. Participants were recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The study findings indicate that it is found that clergy (or in their absence) with patient (or family/friend) beliefs are important in this practice, and this importance in the premise of responding to religious or spiritual needs is adequate. 15 Spiritual Needs for Palliative Patients When the patient goes through a period of palliation or fatal illness, this condition will confront the patient with difficult questions such as "why did this happen to me?" A terminally ill patient may ask this question about his illness, his illness experience, or the meaning of his illness.…”
Section: Spirituality Religion and Philosophy Of Lifementioning
confidence: 99%
“…The study findings indicate that it is found that clergy (or in their absence) with patient (or family/friend) beliefs are important in this practice, and this importance in the premise of responding to religious or spiritual needs is adequate. 15 Spiritual Needs for Palliative Patients When the patient goes through a period of palliation or fatal illness, this condition will confront the patient with difficult questions such as "why did this happen to me?" A terminally ill patient may ask this question about his illness, his illness experience, or the meaning of his illness.…”
Section: Spirituality Religion and Philosophy Of Lifementioning
confidence: 99%
“…The instinctual reaction to the fear generated is then often mediated by religion [2]. Religion and spirituality help individuals make sense of what awaits them near the end of life [3] and help the dying cope with their terminal condition [4]. Given the importance of religion and spirituality at the end of life, palliative care aims to improve the quality of life of the patient and their family and friends through a holistic approach by addressing not just the physical, psychological, emotional, and social needs but also the spiritual and religious needs, making it multidimensional in nature [5,6].…”
Section: Introductionmentioning
confidence: 99%